Space time fractional Ito system with variable coefficients: explicit solution, conservation laws and numerical approximation - Kour, Baljinder; İnç, Mustafa; Arora, Ashish (Emerald Group Publishing Ltd, 2023)
Purpose The purpose of this paper is to present the residual power series method for solving the space time fractional variable coefficients Ito system. Design/methodology/approach A weighted algorithm based on the residual power series method is used numerical solution of the space time fractional Ito system variable coefficients. The authors show that this technique yields the analytical solution of the desired problem in the form of a rapidly convergent series with easily computable components. Findings The authors illustrate that the proposed method produces satisfactory results with respect to the other semi analytical methods. The reliability of the method and the reduction in the size of computational domain give this method a wider applicability. Originality/value This research presents, for the first time, a new modification of the proposed technique for aforementioned problems and some interesting results are obtained.
Keywords: Fractional differential equations; Explicit solution; Conservation laws; Numerical RPS approximation